Polyolefinic nanocomposite foams: Review of microstructure-property relationships, applications, and processing considerations. (January 2022) - Kumar, Anish; Patham, Bhaskar; Mohanty, Smita; Nayak, Sanjay Kumar
In this review, we survey the state of the art on polymeric foams incorporating nano-scale fillers. Particular focus of the review is on foams from polyolefinic nanocomposite formulations incorporating a wide variety of fillers. The nano-scale additives can influence the foam structure and properties in two ways: Firstly, they can act as composite reinforcement to enhance the mechanical properties and functionality of the matrix polymer; and secondly, they can act as foaming-processing aids through modification of the rheological, thermal and crystallization properties of the matrix as well as serving as heterogeneous nucleation sites. Through a combination of these influences, and using advanced processing techniques it is possible to achieve nanocomposite foams that have higher cell density, and more uniform cell size or controlled cell-size distribution. Such controlled foam morphologies, in turn, can yield better specific mechanical properties resulting in more effective light-weighting solutions. Further, the nano-scale additives can impart additional desired functionality resulting in multi-functional foams. In this article, we provide an overview of the mechanical, thermal and a few other relevant functional properties – such as piezoelectric sensitivity, acoustics, and filtration efficiency – of foams prepared using nanocomposite formulations, along with the processing considerations for achieving high quality foams using such materials.